PENGARUH KARAKTERISTIK PERUSAHAAN DAN REGULASI TERHADAP IMPLEMENTASI CORPORATE GOVERNANCE (Studi pada Perusahaan yang Tedaftar di BEI Tahun 2015-2019) - Putri Nabilah; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
This study aims to analyze the influence of company characteristics and regulations on the implementation of corporate governance. This type of research is a correlational research. The data source used is secondary data using documentation techniques. The study population was all companies listed on the IDX in 2015-2019. The samples in this study used a purposive sampling method and were found 35 companies that match the criteria of this study. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that sales growth, ownership concentration, company size and regulation have a positive effect while leverage has a negative effect. Simultaneously the variables in this study have a positive effect.Keywords: Sales Growth, Ownership Concentration, Leverage, Company Size, Regulation, Corporate Governance Implementation